1997
DOI: 10.1128/aac.41.9.1985
|View full text |Cite
|
Sign up to set email alerts
|

Nephrotoxicity of vancomycin and drug interaction study with cilastatin in rabbits

Abstract: The nephrotoxic effects of vancomycin hydrochloride (VCM) and the potential drug-drug interaction with cilastatin sodium (CS) were examined in rabbits. The aim of the study was to measure the possible dose-related suppressive effects or elimination by cilastatin of the adverse reactions generated by vancomycin in the kidneys of rabbits. To clarify the interactions of these two drugs, we examined the nephrotoxicity and pharmacokinetics of VCM in the rabbit when administered alone and when coadministered with CS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 11 publications
4
42
1
Order By: Relevance
“…Increased urinary NAG excretion demonstrates the cell injury in the renal proximal tubules (Yoshiyama et al, 2001;Oktem et al, 2005;Ozguner et al, 2005). In VCM administrated rats, a significant increase of NAG was demonstrated in different studies (Toyoguchi et al, 1997;Yoshiyama et al, 2001;King and Smith, 2004). In the present study, although glomerular function indicators such as serum Cr and BUN were normal, higher urinary NAG activity was found in VCM-group indicating that VCM might cause an impact in the renal proximal tubule.…”
Section: Histopathologic Parameterscontrasting
confidence: 65%
“…Increased urinary NAG excretion demonstrates the cell injury in the renal proximal tubules (Yoshiyama et al, 2001;Oktem et al, 2005;Ozguner et al, 2005). In VCM administrated rats, a significant increase of NAG was demonstrated in different studies (Toyoguchi et al, 1997;Yoshiyama et al, 2001;King and Smith, 2004). In the present study, although glomerular function indicators such as serum Cr and BUN were normal, higher urinary NAG activity was found in VCM-group indicating that VCM might cause an impact in the renal proximal tubule.…”
Section: Histopathologic Parameterscontrasting
confidence: 65%
“…Although imipenem could be partially responsible for this effect, this hypothesis seems unlikely since imipenem is known to cause acute proximal tubular necrosis 26 . In contrast, cilastatin has been reported to alleviate the nephrotoxicity of other drugs, such as vancomycin and cisplatin 15,16 . We have previously reported that both cyclosporin and FK506 have a dose-dependent, direct toxic effect on primary cultures of proximal tubules.…”
Section: Figure 2 Meta-regression Analysis Of Clinical Studies To Comentioning
confidence: 92%
“…Although cilastatin has also been reported to alleviate the nephrotoxicity of vancomycin and cisplatin in animal models 15,16 , the lack of plausible mechanisms for cilastatin renal protection and the unavailability of pure cilastatin for human use shadowed the potential clinical relevance of cilastatin use. Two recent findings have reactivated interest in this area.…”
Section: Introductionmentioning
confidence: 98%
“…Administration of superoxide dismutase reduced the extent of toxic injury. In rabbits, treatment with cilastatin inhibited renal tubular uptake of vancomycin and reduced nephrotoxicity [10]. This reduction of nephrotoxicity has also been demonstrated in humans receiving concomitant treatment with imipenem-cilastatin [11].…”
Section: Discussionmentioning
confidence: 91%
“…Although the mechanism of nephrotoxicity is unclear, several studies have suggested a direct toxic effect of vancomycin on the renal tubular cells [5,[8][9][10]. Kidney biopsy following vancomycin administration to rabbits has revealed dilation of proximal tubules, destruction of renal tubule cells, swollen mitochondria, increased numbers of vacuoles and lysosomes, and abnormal nuclei [10].…”
Section: Discussionmentioning
confidence: 98%